Pengaruh Likuiditas, Profitabilitas, dan Leverage Terhadap Stabilitas Keuangan: Menguji Interaksi Ukuran Perusahaan - Alif, Gattuso Putra; Shalahuddin, Ahmad; Mustika, Uray Ndaru; Syahputri, Anggraini (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Financial stability refers to the condition of a company's financial health in which it is able to allocate its financial resources effectively to prevent disruptions to the financial system. This study examines the effect of leverage, profitability, and liquidity on the financial stability of companies in the property and real estate industry, with corporate governance serving as a moderating variable. The data used in this research are derived from the annual reports of property and real estate companies listed on the Indonesia Stock Exchange for the period 2019–2023. The study involves a population of 150 companies, from which a sample of 30 companies was selected over a five-year analysis period. Data analysis was conducted using panel data regression with the assistance of EViews 12 software. Overall, this research makes a significant contribution to the financial management literature, particularly in understanding the role of company characteristics in strengthening the relationship between financial performance indicators and corporate stability. The findings are also expected to serve as a strategic reference for company management and investors in making more prudent and data-driven financial decisions.